Recent advances in the use of osmotic dehydration of fruits: a bibliometric review (SCIÉNDO INGENIUM, 2026)
This research aims to conduct a bibliometric analysis of the application of the osmotic dehydration process in fruits. A quantitative approach using bibliometric and scientometric techniques was used, utilizing a collection of 627 articles (2015–2025). Using Bibliometrix (R) and VOSviewer, co-authorship networks, thematic groups, conceptual evolution, and productivity and impact indicators were identified. The results show that dehydration technology is a dynamic line of research where multiple variables converge, such as processing techniques, nutritional and sensory quality, as well as structural characteristics of foods. The studies highlight numerous opportunities for synergy, referring to the application of ultrasound or vacuum during osmosis to improve efficiency without compromising quality.
Keywords: Application; optimization; osmotic dehydration; fruits